Penambahan ekstrak umbi bit (Beta vulgaris L.) sebagai antioksidan dalam sabun mandi cair - Dewi Fortuna Ayu; Vonny Setiaries Johan; Nico Wardana (AGROINTEK, 2025)
Beetroot (Beta vulgaris L.) is a natural source of antioxidants that can be added to liquid bath soap.  The use of an appropriate amount of beetroot is expected to function as an antioxidant and meet the quality requirements of liquid bath soap.  This study aimed to determine the optimal amount of beetroot extract in liquid bath soap to maximize the quality and antioxidant activity of liquid bath soap. Five treatments and three replications were employed in the study's complete randomization design. In 100 g of liquid bath soap formula, the beetroot extract volumes S0 (0 ml), S1 (5 ml), S2 (10 ml), S3 (15 ml), and S4 (20 ml) were added as the treatments. Analysis of variance was used to statistically examine the data, and then Duncan's New Multiple Range Test at a level of 5% was applied. According to the study, adding beetroot extract substantially impacted several variables, including density, pH, viscosity, descriptive test, hedonic test, and antioxidant activity. The best liquid bath soap treatment, S4, had a density of 1.07 g/ml, zero free alkalies, a pH of 9.96, 88.00% foam stability, a viscosity of 179.86 cP, and IC50 of 88.13 ppm. The result of a descriptive test on liquid bath soap showed that the soap had brown color and beetroot flavor.  The use of beetroot in liquid bath soap provided an alternative antioxidant to prevent premature aging of the skin with modification in the fragrance ingredient addition.